The origins of you : how breaking family patterns can liberate the way we live and love - Pharaon, Vienna (G.P. Putnam's Sons, 2023)
"From licensed therapist and popular Instagram relationship expert Vienna Pharaon (@mindfulmft, +631K followers) comes a profound guide to understanding and overcoming wounds from your Family of Origin-the foundation of how we relate to others, ourselves, and the world around us"--